Tissue is the issue and tissue competition. Re-biopsy for mutation T790: where and why? - Zarogoulidis, Paul (Clin Transl Med, 2017)
Lung cancer is still the leading cause of death among all cancers. During the last 15 years, pharmacogenomics of lung cancer have established targeted therapy with tyrosine kinase inhibitors (TKIs) for epidermal growth factor receptor (EGFR) positive patients in adenocarcinoma or mixed adenosquamus lung cancer patients. However; while novel drugs are released in the market, at the same time novel mutations are observed after tyrosine kinase inhibitor administration. Recently the novel mutation T790 was observed and is highly prevalent in patients already treated with a TKI. A new drug targeting this mutation is already on the market, however; the most important factor for successful treatment in these patients, is adequate tissue re-sampling so that novel mutations can be detected.